2015
DOI: 10.5153/sro.3768
|View full text |Cite
|
Sign up to set email alerts
|

Un/making the British Asian Male Athlete: Race, Legibility and the State

Abstract: This article explores the social construction of the British Asian male sport star. It foregrounds an analysis of the racial state, primarily its biopolitical function in (re)affirming racialised models of citizenship and contemporary hierarchies of belonging. Drawing on conceptualisations of legibility, the article argues that this relationship between race and the state is necessary to understand the processes by which such athletes are made intelligible in the popular imagination. Empirically, the article f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The racialisation of South Asian individuals across Western sporting discourse is also significant in its uniformity. British Asian athletes, for example, are regularly constructed as 'illegible' in relation to normative conceptions of British sportsmen/women (Burdsey 2015).…”
Section: Sport and Ethno-racial Formationmentioning
confidence: 99%
“…The racialisation of South Asian individuals across Western sporting discourse is also significant in its uniformity. British Asian athletes, for example, are regularly constructed as 'illegible' in relation to normative conceptions of British sportsmen/women (Burdsey 2015).…”
Section: Sport and Ethno-racial Formationmentioning
confidence: 99%
“…K. Johansson & Lee, 2014;N. Johansson & Metzger, 2016;Kutay, 2015;Avritzer, 2008;Oser, 2010;Zimmermann & Favell, 2011); (b) the state, (Aksartova, 2003); (c) in democratic ways (Burdsey, 2015;Evans, 2012;Kamali, 2001Kamali, , 2007Lipset, 1994;Pousadela, 2016); and (d) through the common good/social capital (Cederström & Fleming, 2016;Clemens, 2015;Graddy & Wang, 2009;Pardo, 1995;Silber, 1998;Silver, 1998Silver, , 2001.Within this segment of literature, civil society organizations' legitimacy is mainly investigated as belonging to a specific field within the larger civil society, by which they and their position vis-à-vis the state and market can be established. This body of research takes as its starting point legitimacy as the representative condition of civil society.…”
Section: Legitimacy As Representation Versus Legitimacy As Instrumentmentioning
confidence: 99%
“…4 These figures are significantly disproportionate to the Indo-Fijian share of the country’s female population, which accounts for roughly 34% of that total (Fiji Bureau of Statistics, 2017). Difficulty in connecting with local sporting archetypes is not new for the international Indian diaspora (Burdsey, 2015; Ratna, 2011; Thangaraj, 2015). But it does raise questions about how this global trend is impacted by local conditions.…”
Section: Background and Purposementioning
confidence: 99%
“…For example, in his ethnography into Asian American men, Thangaraj (2015) found that through sport (pickup basketball) he was able to understand the agency of the players in their re-making of South Asian masculinity, this countering broader, racialised discourses about this group in North American culture. In that respect, sport can be a useful analytical field that depicts both local realities and agency which connects to broader socio-cultural forces in pursuit of praxis (see also Burdsey, 2015; Ratna, 2011).…”
Section: Sportive Agency and Crfmentioning
confidence: 99%